A simulation model of reinforced concrete beam containing expanded polystyrene beads (EPS) and palm oil fueled ash (POFA) using finile element method - Ambok Lalak, Daing Muhammad Irfim; Osman, Mohamad Hairi; Wan Jusoh, Wan Amizah; A Rahman, Noor Khazanah; Adnan, Suraya Hani; Mohd Jeni, Mohd Luthfi; Hanipah, Mohd Hafizal; Yahya, Nur Faezah; Tami, Hannifah; Salim, Salman; Mat Nor, Ahmad Hakimi; Mat Nor, Ahmad Hakimi (Penerbit UTHM, 2020)
In this study, Expanded Polystyrene bead (EPS) and Palm Oil Fuelled Ash (POFA) will be used to replace several percents of cement and aggregate in reinforced concrete beam construction. EPS can produce lightweight concrete, and the use of POFA can produce high strength concrete and can also reduce waste disposal. The reinforced concrete beams were analysed using computer software called ABAQUS. The main reason Abaqus software is used as analytics software for this project is that the software is designed specifically for analyzing advanced structural and heat transfer. It is designed for both linear and nonlinear pressure analyses for both tiny and huge structures. This software can also be used to analyze the proposed reinforced concrete beam failure pattern of EPS and POFA. The percentage of EPS and POFA were 40% to 60% in concrete as replacement material. The information obtained from Abaqus is then used to verify the experimental results. The data also contains the appropriate percentage of EPS and POFA in the reinforced concrete beam where performance in terms of bending, pressure, and failure pattern is at maximum. The result shows decrease performance of RC beam containing 40-60% EPS and POFA.